Cosmic ray detection with the LOFAR radio telescope - Terveer, Karen; Bouma, Sjoerd; Buitink, S.; Corstanje, A.; Desmet, M.; Falcke, H.; Hare, B. M.; Hörandel, J. R.; Huege, T.; Karastathis, N.; Laub, Philipp; Mulrey, K.; et al. (Proceedings of Science, 2024)
The LOw Frequency ARray (LOFAR) has successfully measured cosmic rays for over a decade now. With its dense core of antenna fields in the Netherlands, it is an ideal tool for studying the radio emission from extensive air showers in the 1016 eV to 1018.5 eV range. Every air shower is measured with a small particle detector array and hundreds of antennas, which sets LOFAR apart from other air shower arrays. We present our current achievements and progress in reconstruction, interpolation, and software development during the final phases of measurement of LOFAR 1.0, before the LOFAR array gets a significant upgrade, including also plans for the final data release and refined analyses.
CRIS-Team Scopus Importer:2025-02-04

Cosmic ray observations with the Square Kilometre Array - Buitink, S.; Bouma, Sjoerd; Bray, J.; Corstanje, A.; Desmet, M.; Falcke, H.; Hare, B. M.; Hörandel, J. R.; Huege, T.; James, C. W.; Karastathis, N.; Laub, Philipp; et al. (Proceedings of Science, 2024)
The low-frequency part of the SKA, to be built in Australia, will have an extremely high antenna density of roughly 60,000 antennas within one square kilometer, and is the perfect site for high-resolution studies of air showers. Individual showers will be observed with thousands of antennas simultaneously. The depth of shower maximum Xmax can be reconstructed with a resolution of 10 g/cm2 using methods currently used by LOFAR and the Pierre Auger Observatory. However, the high-resolution SKA data allows the development of new methods that can reconstruct more features of the longitudinal development of air showers, such as the shower length or double-bump profiles. This allows new constraints on both the mass composition and hadronic shower physics. Here we discuss the status of the SKA cosmic-ray program and simulation studies of its capabilities.
CRIS-Team Scopus Importer:2025-02-04

Cosmic rays with LOFAR 2.0 - what’s next? - Mulrey, K.; Bouma, Sjoerd; Buitink, S.; Corstanje, A.; Desmet, M.; Falcke, H.; Hare, B. M.; Hörandel, J. R.; Huege, T.; Jhansi, V. B.; Karastathis, N.; Laub, Philipp; et al. (Proceedings of Science, 2024)
The LOFAR radio telescope has been used to measure radio emission from cosmic-ray air showers in the 1016.5−1018 eV range for over a decade. LOFAR is currently undergoing an upgrade (LOFAR 2.0) which will enable continuous observation and a tenfold increase in data rate, as well as a wider measurement bandwidth. We have recently doubled the size of the particle detector triggering array located at LOFAR to maximize the benefits of this upgrade. We are also developing new analysis techniques and data pipelines in order to best utilize the new influx of data and increase the energy range in which we measure. In this contribution, we present our plans for the LOFAR 2.0 cosmic-ray observation program.
CRIS-Team Scopus Importer:2025-02-04

Solar flare observations with the Radio Neutrino Observatory Greenland (RNO-G) - Agarwal, S.; Aguilar, J. A.; Ali, S.; Allison, P.; Betts, M.; Besson, D.; Bishop, A.; Botner, O.; Bouma, Sjoerd; Buitink, S.; Cataldo, Maddalena; Clark, B. A.; et al. (Astroparticle Physics, 2025)
The Radio Neutrino Observatory – Greenland (RNO-G) seeks discovery of ultra-high energy neutrinos from the cosmos through their interactions in ice. The science program extends beyond particle astrophysics to include radioglaciology and, as we show herein, solar observations, as well. Currently seven of 35 planned radio-receiver stations (24 antennas/station) are operational. These stations are sensitive to impulsive radio signals with frequencies between 80 and 700 MHz and feature a neutrino trigger threshold for recording data close to the thermal floor. RNO-G can also trigger on elevated signals from the Sun, resulting in nanosecond resolution time-domain flare data; such temporal resolution is significantly shorter than from most dedicated solar observatories. In addition to possible RNO-G solar flare polarization measurements, the Sun also represents an extremely useful above-surface calibration source. Using RNO-G data recorded during the summers of 2022 and 2023, we find signal excesses during solar flares reported by the solar-observing Callisto network and also in coincidence with ∼2/3 of the brightest excesses recorded by the SWAVES satellite. These observed flares are characterized by significant time-domain impulsivity. Using the known position of the Sun, the flare sample is used to calibrate the RNO-G absolute pointing on the radio signal arrival direction to sub-degree resolution. We thus establish the Sun as a regularly observed astronomical calibration source to provide the accurate absolute pointing required for neutrino astronomy.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Calibration; Radio telescopes; Solar flares; UHE neutrinos

Thunderstorm Charge Distribution Determination Using Cosmic Rays Induced Air Showers and Lightning Imaging at LOFAR - Trinh, T. N.G.; Scholten, O.; van Loon, R.; Hare, B. M.; Assink, J. D.; Bouma, Sjoerd; Buitink, S.; Corstanje, A.; Cummer, S.; Desmet, M.; Dwyer, J.; Falcke, H.; et al. (Geophysical Research Letters, 2025)
The LOw Frequency ARray (LOFAR) radio telescope possesses the unique capability to measure ultra-high energy cosmic rays as well as image lightning discharges. This study presents a comparison between the inferred thunderstorm charge structures derived from cosmic-ray measurements and from lightning flashes. Our results show a basic triple-layered distribution: a positive upper layer, a main negative layer, and a positive lower layer. However, our cosmic-ray measurement shows a bottom-heavy structure, where the charge in the upper positively charged layer is smaller than that in the lower one. This is consistent with practically all lightning observations with LOFAR, showing well-developed negative leader structures at altitudes below those where positive leaders are seen. This is very different from the vast majority of thundercloud charge structures seen around the world.
CRIS-Team Scopus Importer:2025-05-16
Keywords: cosmic-ray air showers; lightning imaging; thunderstorm charge structures